The Analysis of Musculoskeletal Complaints and the Influencing Factors on Shoe-Craftsmen in Leather Crafs Center, Magetan - Ekawati Wasis Wijayati; Nurwijayanti Nurwijayanti; Koesnadi Koesnadi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
Working posture that is not appropriately done and maintained in long period/ duration can cause complaints or health problems, especially musculoskeletal complaints. The emergence of musculoskeletal complaints can lead to fatigue and even concentration disorder in working that can result in decreasing of working productivity. The purpose of this study is to analyze musculoskeletal complaints and the influencing factors on shoe-craftsmen in Magetan leather craft center. The research design that is used is quantitative research using analytic observational method and cross sectional approach. The sampling technique is proportional qluster random sampling with 84 respondents of shoes-craftsmen in Sawo Magetan leather craft center. The data of the research were analyzed by ordinal regression test. The result of statistical analysis using ordinal regression shows that p value = 0,000 (p <0,05) which means there is influence of working posture, duration, period of work, body size / BMI toward musculoskeletal complaints on shoe-craftsmen Magetan leather craft center. The strongest influence is working posture, period of work and duration. High-risk working postures that is performed continuously over a long period of time will increase the risk of musculoskeletal complaints, so it is necessary to take corrective action posture with ergonomic considerations.